Comparison of clinical features between Chlamydia psittaci and Legionella - Chen, Jiamei; Yang, Libing; Liu, Yuni; Zhou, Jianliang; Li, Yongzhong; Wang, Jin; Zheng, Yixiang (Frontiers in Medicine, 2025)
ObjectivesTraditional diagnostic methods have difficulty distinguishing between Chlamydia psittaci (C. psittaci) pneumonia and Legionella pneumonia (L. pneumonia). This study aims to delineate the differences between C. psittaci pneumonia and L. pneumonia.MethodsThis retrospective analysis included 71 cases of C. psittaci pneumonia and 21 cases of L. pneumonia, all confirmed via next-generation sequencing (NGS). We systematically collected and compared data on clinical characteristics, laboratory findings, chest CT imaging, bronchoscopic observations, and prognostic outcomes between the two groups.ResultsIn the C. psittaci pneumonia cohort, 64 patients (91.4%) had an opportunity to contact with poultry, with a maximum temperature of mean 39.6 °C. Additionally, 23 patients (32.4%) experienced dyspnea, and 57 patients (80.3%) exhibited relative bradycardia. Compared to patients with L. pneumonia, those with C. psittaci pneumonia had lower leukocyte counts, neutrophil counts, mononuclear cell counts, systemic inflammatory response index (SIRI), and urea levels, while lymphocyte-to-monocyte ratio (LMR), glutamic-pyruvic transaminase (ALT), glutamic oxaloacetic transaminase (AST), and creatine kinase (CK) levels were elevated. Next-generation sequencing (NGS) plays a crucial role in the early diagnosis of infectious pathogens. Multivariate analysis revealed differences in underlying diseases, residing in countryside, relative bradycardia, and LMR between the two groups.ConclusionSeveral characteristics aid in differentiating C. psittaci pneumonia from L. pneumonia, including exposure to poultry, relative bradycardia, some infection indicators, ALT, AST, and CK. NGS addresses the limitations of traditional diagnostic methods. The early application of NGS facilitates the diagnosis of atypical pneumonia. Multivariate regression analysis suggested that underlying diseases, residing in countryside, relative bradycardia, and LMR is significant in differentiating C. psittaci pneumonia and L. pneumonia.